2023
DOI: 10.3390/plants12020303
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Genomic Prediction on Plant Architecture Traits in Sweet Corn and Waxy Corn

Abstract: Sweet corn and waxy corn has a better taste and higher accumulated nutritional value than regular maize, and is widely planted and popularly consumed throughout the world. Plant height (PH), ear height (EH), and tassel branch number (TBN) are key plant architecture traits, which play an important role in improving grain yield in maize. In this study, a genome-wide association study (GWAS) and genomic prediction analysis were conducted on plant architecture traits of PH, EH, and TBN in a fresh edible maize popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Bayes-type models integrate the variance of the effect values for each marker or chromosome segment as a prior distribution to improve prediction accuracy. We found that the prediction accuracy range for TW was 0.20-0.39, close to the precision for tassel-related traits in previous studies (0.25-0.48) [29,30].…”
Section: Genome-wide Selection Predictionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bayes-type models integrate the variance of the effect values for each marker or chromosome segment as a prior distribution to improve prediction accuracy. We found that the prediction accuracy range for TW was 0.20-0.39, close to the precision for tassel-related traits in previous studies (0.25-0.48) [29,30].…”
Section: Genome-wide Selection Predictionsupporting
confidence: 86%
“…Xu et al utilized the ridge regression best linear unbiased prediction (rrBLUP) model for GS of tassel length, tassel primary branch number, tassel secondary branch number, and tassel branch number, with prediction accuracies of 0.36, 0.41, 0.28, and 0.38, respectively [29]. Dang et al also employed the rrBLUP model for GS on tassel branch number in sweet corn and waxy corn, discovering that increasing the number of markers significantly associated with the target trait led to a notable improvement in prediction accuracy [30]. As the size of the training group increased from 10% to 90% of the total number of markers, the prediction accuracy for tassel branch number increased from 0.16 to approximately 0.48.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that GAs could inhibit the expression of ZmMYBr41 and ZmMYBr87 to activate the expression of ZmHCT8 for modulating the accumulation of 5-O-caffeoylshikimic acid in lignin biosynthesis ( Figure 8 ). ZmMYBr41 turns out to be a gene associated with plant height [ 84 ], and ZmMYBr87 is related to cell wall synthesis [ 85 ], which further proves the involvement of ZmMYBr41 and ZmMYBr87 in regulating cell wall synthesis during leaf cell growth.…”
Section: Discussionmentioning
confidence: 98%